2022
DOI: 10.14218/jcth.2022.00120
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin is a Potential Immunomodulator for Inhibiting Liver Fibrosis by Inhibiting the cGAS-STING Pathway

Abstract: Background and Aims:Naringenin is an anti-inflammatory flavonoid that has been studied in chronic liver disease. The mechanism specific to its antifibrosis activity needs further investigation This study was to focused on the cyclic guanosine monophosphate-adenosine monophosphate synthase (cGAS) pathway in hepatic stellate cells and clarified the antifibrosis mechanism of naringenin. Methods: The relationship between the cGAS-stimulator of interferon genes (STING) pathway and liver fibrosis was analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Methylpyrazole (G140) or 2‐aminopyridine (G150), reported by Lama, have the exact mechanism as described above and were able to show inhibition of cGAS in THP1 cells and human macrophages 108 . At the same time, Naringenin, which is often used as an antioxidant and free radical scavenger, was also able to bind to the active site of cGAS, reducing the mRNA levels of IL‐1β, IL‐6, NF‐κB, and IL‐8 in LX2 cells, and also dose‐dependently reducing the expression of IRF3 protein 109 …”
Section: Inhibitors Of Cgas‐sting Signaling Pathwaymentioning
confidence: 75%
See 1 more Smart Citation
“…Methylpyrazole (G140) or 2‐aminopyridine (G150), reported by Lama, have the exact mechanism as described above and were able to show inhibition of cGAS in THP1 cells and human macrophages 108 . At the same time, Naringenin, which is often used as an antioxidant and free radical scavenger, was also able to bind to the active site of cGAS, reducing the mRNA levels of IL‐1β, IL‐6, NF‐κB, and IL‐8 in LX2 cells, and also dose‐dependently reducing the expression of IRF3 protein 109 …”
Section: Inhibitors Of Cgas‐sting Signaling Pathwaymentioning
confidence: 75%
“…108 At the same time, Naringenin, which is often used as an antioxidant and free radical scavenger, was also able to bind to the active site of cGAS, reducing the mRNA levels of IL-1β, IL-6, NF-κB, and IL-8 in LX2 cells, and also dose-dependently reducing the expression of IRF3 protein. 109 Steinhagen first proposed the cGAS inhibitor A151, which is capable of blocking self-DNA and suppressive oligodeoxynucleotides containing repetitive TTAGGG motifs in mammalian telomeres, 110 is dependent on telomeric sequences and phosphorothioates and inhibits the production of type I IFN by human monocytes through competing with DNA to prevent cGAS activation. 111 Suramin was also able to replace DNA bound to cGAS and inhibit the activity of the cGAS enzyme, while the addition of suramin to THP1 cells was shown to reduce the levels of IFNβ mRNA and protein.…”
Section: Cgas-targeted Inhibitorsmentioning
confidence: 99%
“…Naringenin, with significant anti-inflammatory and antitumor properties [ [42] , [43] , [44] ], has been shown to reduce liver injury and ECM deposition in animal models of hepatotoxicity and CCl 4 -induced liver fibrosis [ 28 ]. Our findings revealed that naringenin reduced HSC viability in a concentration- and time-dependent manner without affecting hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Naringenin (4,5,7-trihydroxyflavone), a flavonoid compound abundant in plants, exhibits a spectrum of pharmacological activities, including anti-inflammatory, antitumor, and immunomodulatory effects [ [24] , [25] , [26] , [27] ]. Although naringenin has demonstrated efficacy in mitigating liver fibrosis induced by carbon tetrachloride, a comprehensive understanding of its underlying mechanisms is lacking [ 28 , 29 ]. In this study, a bile duct ligation (BDL) mouse model was used to investigate the in vivo therapeutic effects of naringenin.…”
Section: Introductionmentioning
confidence: 99%
“…68 Naringenin was shown to reduce liver inflammation and HSC activation by inhibiting the cGAS-STING signaling pathway, improving liver fibrosis. 31 Sorafenib may attenuate the signal transduction of the STING pathway by inhibiting the dimerization of STING and the recruitment of TBK1 and IRF3, thereby alleviating liver inflammation and fat accumulation induced by palmitic acid. 69,70 Bifidobacterium triple live bacteria powder relieves HFD-induced NAFLD by inhibiting the expression of STING, thereby inhibiting the release of TNF-α, IL-1β, IL-6, IFN-β and p-NF-κB p65 induced by macrophages.…”
Section: Sting Agonists and Inhibitors For Treating Nafldmentioning
confidence: 99%